Net clinical benefit of hospitalization versus outpatient management of patients with acute pulmonary embolism. (25th February 2017) - Roy, P.‐M.; Corsi, D. J.; Carrier, M.; Theogene, A.; de Wit, C.; Dennie, C.; Le Gal, G.; Delluc, A.; Moumneh, T.; Rodger, M.; Wells, P.; Gandara, E.
Abstract : Essentials Clinical benefit of hospitalization vs. outpatient treatment in pulmonary embolism (PE) is unknown. We performed a propensity matched cohort study of hemodynamically stable PE patients. Regardless of the risk assessment, hospitalized patients had the highest rate of adverse event. If confirmed, ambulatory care of normotensive PE patients may be preferred whenever possible. Summary: Background: The decision to hospitalize or not patients with acute pulmonary embolism (PE) is controversial. Despite the advantages of close monitoring, hospitalization by itself may lead to in‐hospital complications and potentially worsen the prognosis of PE patients. Objectives: To determine the net clinical benefit of hospitalization vs. outpatient management of normotensive patients with acute pulmonary embolism (PE). Methods: Retrospective cohort propensity score analysis (radius marching with replacement). Hemodynamically stable PE patients treated as outpatients or inpatients were matched to balance out differences for 28 patient characteristics and known risk factors for adverse events. The primary outcome was the rate of adverse events at 14 days, including recurrent venous thromboembolism, major bleeding or death. Results: Among 1127 eligible patients, 1081 were included in the matched cohort, 576 treated as inpatients and 505 as outpatients. The 14‐day rate of adverse events was 13.0% for inpatients and 3.3% for outpatients (adjusted OR, 5.07; 95% CI, 1.68–15.28). The 3‐month rate was 21.7% for inpatients and 6.9% for outpatients (OR, 4.90; 95% CI, 2.62–9.17). In the high‐risk subgroup (Pulmonary Embolism Severity Index class III‐V; n = 597), the 14‐day rate of adverse events was 16.5% for hospitalized patients vs. 4.5% for outpatients (OR, 4.16; 95% CI, 1.2–14.35). Conclusion: Outpatient treatment of hemodynamically stable PE patients seems to be associated with a lower rate of adverse events than hospitalization and, if confirmed, may be considered as first‐line management in patients not requiring specific in‐hospital care, regardless of their initial risk stratification, if proper outpatient care can be provided.